How Social Support and Grit Influence Entrepreneurs’ Innovative Behavior in Micro and Small Enterprises: The Mediating Role of Creativity - Matrissya Hermita; Nurlintang Putri Ayuning Rizal; Budi Hermana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Business is characterized by an uncertain and fast-growing environment, so innovation is important in that sphere. The study aims to examine the influence of social support and grit on innovative work behaviour with creativity as a mediation role among entrepreneurs in micro and small enterprises. A survey questionnaire was used in this research to gather data from various region in Indonesia. There were 130 respondents which have been running their business for at least two years gathered by accidental sampling technique. Data analysis used two-model of multiple regression and path analysis was used for determine the mediation role. The results showed that there was an influence between social support, grit with mediation of creativity on innovative behavior. This means that social support and grit can affect an individual's level of creativity, and creativity can drive innovative behavior in the workplace. The result suggests that creativity can act as a mediation variable. Grit is known to be the dominant variable with a 47.1% contribution in influencing innovative behavior through creativity, and the rest is influenced by other factors outside the study, such as job characteristic.